2009
DOI: 10.1139/g09-002
|View full text |Cite
|
Sign up to set email alerts
|

Mutation scanning and genotyping by high-resolution DNA melting analysis in olive germplasm

Abstract: The application of high-resolution melting (HRM) analysis of DNA is reported for scanning and genotyping Olea europaea germplasm. To test the sensitivity of the method, a functional gene marker, phytochrome A (phyA), was used, since this gene is correlated with important traits for the ecology of the species. We have designed a set of oligos able to produce amplicons of 307 bp to scan for the presence of single polymorphic mutations in a specific phyA fragment encompassing the chromophore attachment site (Cys3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Until a recently published study (Kaya et al 2013), only a small number of SNP loci had been identified in olives (Hakim et al 2010;Macedo et al 2009;Muleo et al 2009;Reale et al 2006). Kaya's study used deep sequencing for the identification of 2987 SNPs in olives (Kaya et al 2013 Fig.…”
Section: Snps Identification Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Until a recently published study (Kaya et al 2013), only a small number of SNP loci had been identified in olives (Hakim et al 2010;Macedo et al 2009;Muleo et al 2009;Reale et al 2006). Kaya's study used deep sequencing for the identification of 2987 SNPs in olives (Kaya et al 2013 Fig.…”
Section: Snps Identification Strategymentioning
confidence: 99%
“…Various DNA markers have been used in these studies including restriction fragment length polymorphism (RFLP) (Bazakos et al 2012;Besnard and Berville 2002), amplified fragment length polymorphism (AFLP) (Albertini et al 2011;Angiolillo et al 1999;Baldoni et al 2006), random amplified polymorphic DNA (RAPD) (Awan et al 2011;Leva and Petruccelli 2012;Parra-Lobato et al 2012), sequence-characterized amplified regions (SCAR) (Marieschi et al 2011), DaRT (Domínguez-García et al 2012, SSR (Beghe et al 2011;Biton et al 2012;Corrado et al 2011;Delgado-Martinez et al 2012;Ercisli et al 2011;Rehman et al 2012;Rotondi et al 2011) and single nucleotide polymorphism (SNP) Hakim et al 2010;Macedo et al 2009;Muleo et al 2009;Reale et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, HRMA has mostly been applied in clinical studies of gene mutations in cancer cells (Simi et al 2008;Jones et al 2008), and also to detect viruses (Varillas et al 2010) and bacteria causing lethal food-borne infections in humans (Wang et al 2010). In plants HRMA has been experimentally used to detect novel alleles in barley (Hofinger et al 2009), to analyse olive germplasm (Muleo et al 2009), to differentiate grapevine and olive cultivars (Mackay et al 2008), and to identify bilberry samples (Jaakola et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…HRM is typically used for high-throughput genotypic screening of multiple TILLING mutant libraries of complex crop genomes. HRM has been successfully used to identify mutants and point mutations in Brassica (Lochlainn et al 2011 ), wheat (Botticella et al 2011 ), peach (Chen and Wilde 2011 ), olive (Muleo et al 2009 ), etc.…”
Section: Hrm ( H Igh-r Esolution M Elting) Genotypingmentioning
confidence: 99%